The Robot Steps in: from Normative Ethics (‘ought’) to Prospective Ethics (‘coming to be’) – An Introduction to the Films Westworld – Blade Runner – I, Robot – A.I. Artificial Intelligence - Martins, José (2020)
The present paper reports the role played by the cinema cycle associated to the International Conference on Robot Ethics (ICRE 2015), that was open to the general public. Reflecting on the grounding motivations leading to this international conference, the paper analyses the role played by fiction and film industry in the definition and anticipation of a future world where humans and intelligent machines will coexist